2018
DOI: 10.1128/mcb.00181-17
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A/CREB Signaling Prevents Adriamycin-Induced Podocyte Apoptosis via Upregulation of Mitochondrial Respiratory Chain Complexes

Abstract: Previous work showed that the activation of protein kinase A (PKA) signaling promoted mitochondrial fusion and prevented podocyte apoptosis. The cAMP response element binding protein (CREB) is the main downstream transcription factor of PKA signaling. Here we show that the PKA agonist 8-(4-chlorophenylthio)adenosine 3',5'-cyclic monophosphate-cyclic AMP (pCPT-cAMP) prevented the production of adriamycin (ADR)-induced reactive oxygen species and apoptosis in podocytes, which were inhibited by CREB RNA interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…We also found that overexpression of wild-type CREB, but not the CREB S133A mutant, in C2C12 myotubes upregulated Pgc-1α expression (Fig. 2e), which aligned with the previous report that CREB was a transcriptional regulator of PGC-1α expression [24].…”
Section: Exercise-mimic Increased Fndc5 and Pgc-1α Expression In Myotsupporting
confidence: 92%
“…We also found that overexpression of wild-type CREB, but not the CREB S133A mutant, in C2C12 myotubes upregulated Pgc-1α expression (Fig. 2e), which aligned with the previous report that CREB was a transcriptional regulator of PGC-1α expression [24].…”
Section: Exercise-mimic Increased Fndc5 and Pgc-1α Expression In Myotsupporting
confidence: 92%
“…Protein samples were boiled to denature under reducing condition using NuPAGE LDS sample buffer/reducing agent (NP007/NP009, Invitrogen, New York, USA). SDS‐PAGE and immunoblot analyses were performed using standard protocols as described previously . Primary antibodies used in this study were rabbit anti‐human phospho‐PDH(S293) antibody (1:2000; Abcam, Cambridge, UK), rabbit anti‐human PDH antibody (1:2000; Abcam), rabbit anti‐human PDK4 antibody (1:1000, Abcam), rabbit anti‐human PGC‐1α antibody (1:1000, Cell Signaling Technology, Danvers, Massachusetts, USA), phospho‐Drp1(S637) antibody (1:1000, Cell Signaling Technology), phosphor‐Drp1(S616) antibody (1:1000, Cell Signaling Technology), Drp1 antibody (1:1000, Cell Signaling Technology), rabbit anti‐human Mfn‐1 antibody (1:100, Santa Cruz Biotechnology) and mouse anti‐human GAPDH antibody (1:1000, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE and immunoblot analyses were performed using standard protocols as described previously. 10 Primary antibodies used in this study were rabbit anti-human phospho-PDH(S293) antibody…”
Section: Protein Collection and Western Blottingmentioning
confidence: 99%
“…The transcription factors Msn2 and Msn4 are activators of glycolysis [46], and they have also been linked to autophagy and mitochondrial respiration [70,74]. Finally, PKA activity has been closely linked to the control of mitochondrial processes through multiple targets [75][76][77][78][79][80][81]. Therefore, we assessed the structure of the mitochondria using Cit1-GFP in WT and eaf1Δ backgrounds in combination with snf1Δ, msn2msn4Δ, and bcy1Δ (hyperactive PKA) (Fig 5).…”
Section: Mitochondrial Elongation In Eaf1δ Cells Can Be Partially Reversed Upon Deletion Of Bcy1mentioning
confidence: 99%